Opracowanie i analiza komputerowego systemu odtwarzania napięć i prądów - Dąbrowski, Robert
The paper presents design and analysis of computer-based measuring system for realization standard values of voltage and cun-enl. For these purposes two kinds of systems are used. An efficient and expensive one built on high accuracy calibrator, and economical, but less efficient system based on much cheapper average accuracy calibrator, computer and high accuracy multimeter as a standard. Common use of digital multimeters (DMM) requires desi~ of efficient and low cost system, which can be used to standardize and adjust meters under control. For this purpose Author has proposed structure of the economical system. The main features ofthis system are high accuracy and possibly good efficiency comparable with high accuracy calibrator features. Dissertation comprises: models of systems for realization of voltage and cun-ent standard values, analysis of static and dynamic features of these systems, and verification of theoretical results by design and testing physical model of described system.
Keywords: wzorcowanie multimetrów; realizacja wartości wzorcowej; kalibrator; komputerowy system odtwarzania napięć i prądów; model symulacyjny; model fizyczny